MODERNIZATION OF MODERN RUSSIA: INSTITUTIONAL ASPECT (PRINCIPLE OF «EXCHANGE») - A. P. Shitov; L. V. Roubtsova (Модернизация, инновация, развитие, 2016)
Basic directions of the institutional change in the process of modernization of Russia’s post-industrial society are discussed on the basis of macroand microeconomics. Institutions set a system of incentives and direct activities of the subjects to respective channel, which reduces uncertaintyand makes the socio-economic environment more predictable. «Exchange» means a balance of interests of different society groups and sectors that manifests social acceptance of the distribution of resources and social products. System achievement of this goal in Russia consists in transition of its economy from the raw material export pattern to the innovative social-oriented type of development.